Analyzing Second Language Technical Writing: Towards a Systemic Functional Linguistic Based Model - Abdelrahim, Azza A. M. (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
Pedagogies for language and writing instruction informed by systemic functional linguistics (SFL) have gained significant ground throughout second language instruction in the past decade. This paper reports the findings of a study that investigates the effect of using the analysis of technical writing within the systemic functional linguistic framework in developing the rhetorical awareness of second language learners in technical writing. The participants of the study were sixty university students. The study administered a genre analysis test based on SFL and analyzed students’ writing samples to explore second language learners’ rhetorical awareness. The findings demonstrated that analyzing technical genre samples based on the SFL model developed students’ rhetorical awareness. Analyzing technical genre samples helped students become aware of how texts in technical writing are shaped for different purposes, audiences, and context. Furthermore, the students’ rhetorical awareness was transferred to their technical writing. The study therefore offers implications for SFL pedagogies in language and writing instruction.